The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3389/fmicb.2015.01324
|View full text |Cite
|
Sign up to set email alerts
|

Sophorolipids Production by Candida bombicola ATCC 22214 and its Potential Application in Microbial Enhanced Oil Recovery

Abstract: Biosurfactant production using Candida bombicola ATCC 22214, its characterization and potential applications in enhancing oil recovery were studied at laboratory scale. The seed media and the production media were standardized for optimal growth and biosurfactant production. The production media were tested with different carbon sources: glucose (2%w/v) and corn oil (10%v/v) added separately or concurrently. The samples were collected at 24 h interval up to 120 h and checked for growth (OD660), and biosurfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(86 citation statements)
references
References 48 publications
10
72
0
3
Order By: Relevance
“…Extra oil recovery was observed after injecting 4–5 PV of biosurfactant solution, where 24–26% (≅0.5 ml) of So r was produced ( Figure 8 ). Other researchers have reported 20–37% additional oil recovery over the residual oil saturation using cell-free biosurfactant injection in the core-plugs or sand-pack columns (Yakimov et al, 1997; Almeida et al, 2004; Al-Sulaimani et al, 2011a; Darvishi et al, 2011; Joshi and Desai, 2013; Al-Wahaibi et al, 2014; Arora et al, 2014; Elshafie et al, 2015; Joshi et al, 2015; Jha et al, 2016). In present study, the additional oil recovered could be due to mechanisms like reduction in ST/IFT and/or due to wettability alteration at the rock-oil-water interface, as observed during the course of study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extra oil recovery was observed after injecting 4–5 PV of biosurfactant solution, where 24–26% (≅0.5 ml) of So r was produced ( Figure 8 ). Other researchers have reported 20–37% additional oil recovery over the residual oil saturation using cell-free biosurfactant injection in the core-plugs or sand-pack columns (Yakimov et al, 1997; Almeida et al, 2004; Al-Sulaimani et al, 2011a; Darvishi et al, 2011; Joshi and Desai, 2013; Al-Wahaibi et al, 2014; Arora et al, 2014; Elshafie et al, 2015; Joshi et al, 2015; Jha et al, 2016). In present study, the additional oil recovered could be due to mechanisms like reduction in ST/IFT and/or due to wettability alteration at the rock-oil-water interface, as observed during the course of study.…”
Section: Resultsmentioning
confidence: 99%
“…1 μl of the sample-mixture was applied to the steel target plate, and air-dried at room temperature. The spectra were acquired using FlexControl software (v3.3), and FlexAnalysis Software (v3.3, Bruker Daltonics, Bremen, Germany) was used for visualization and initial data processing, as previously reported (Elshafie et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Kim et al [66] Elshafie et al [67] recently demonstrated biosurfactant producing C. bombicola ATCC 22214, for potential applications in oil recovery process. Production medium designed with glucose (2% w/v) and corn oil (10% v/v) successfully utilized by ATCC 22214 and demonstrated reduction in SFT (28.56+0.42 mN/m) and IFT (2.13+0.09 mN/m).…”
Section: Rhamnolipid (Rhl)mentioning
confidence: 99%
“…SPLs are quite stable at 13-15% salinity, pH of wide range (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and temperature upto 100°C. Elshafie et al [67] were successful to demonstrate the role of SPLs in enhancing oil recovery (27.27% of residual oil (Sor) recovery) using core-flooding experimental set up under reservoir conditions. Waste water resulting from dairy industries shows presence of high fat and oil content and therefore disposal of these effluents is extremely challenging.…”
Section: Rhamnolipid (Rhl)mentioning
confidence: 99%
“…Sustainable development has been understood as a variety of concepts and indicators that have matured over time (Ciegis et al, 2015;Lopez et al, 2007;Tiwari and Ibrahim, 2012;Joshi et al, 2015, Frugoli et al, 2015. Particularly critical to wide impact is the shared meaning between global and national levels, which underpins much of the collaborative efforts in policy and business decision-making.…”
Section: Introductionmentioning
confidence: 99%